A novel master–slave teleoperation robot system for diaphyseal fracture reduction: a preliminary study. (16th December 2016) - Li, Changsheng; Wang, Tianmiao; Hu, Lei; Tang, Peifu; Wang, Lifeng; Zhang, Lihai; Guo, Na; Tan, Yiming
Abstract: We developed a novel master–slave teleoperation robot system for diaphyseal fracture reduction. This paper details the mechanical design and the control system as a preliminary study. The fracture reduction accuracy and the performance of the control system are experimentally tested. The mean error in the axial and lateral displacements was below 3 mm; the mean side angle and inward turn errors were below 4°. As a preliminary study, the feasibility of the novel master–slave teleoperation robot system for diaphyseal fracture reduction is verified. The robot system fulfills the reduction requirements in accuracy and operating performance.